UNICEF and the WASH: Analisis Terhadap Peran UNICEF Dalam Mengatasi Masalah Ketersediaan Air Bersih di India - Indra Kusumawardhana; Annisa Asti Nur Auliya (Frequency of International Relations (FETRIAN), 2020)
The Sustainable Development Goals (SDGs) are a blueprint for sustainable global development for equitable growth and prosperity between countries. One indicator of equitable growth is the achievement of adequate access to drinking water, sanitation and hygiene and stopping open defecation (BABS) activities. But the difficulty of access to clean water sources and good sanitation facilities is still an urgent problem in India. More than 50% of the water has been polluted and cannot be consumed. The World Health Organization (WHO) estimates that 97 million Indians do not have access to clean water and proper sanitation. This is caused by various factors, among others, first the habits of the people (culture) who conduct BABS activities. Second, lack of education and human awareness of environmental cleanliness. And the third is the lack of public toilet facilities provided by the government. These problems have a major impact on the health of local communities such as diarrhea and pneumonia. Efforts by the Indian government to solve these problems have yet to produce a significant impact. So that the United Nations (UN) opened an open working group to formulate proposals related to global development planning on clean water and sanitation supported by UNICEF through the WASH (Water, Sanitation, and Hygiene) Program. The implementation of this program is aimed at overcoming the impact of problems that give special focus to children. This research will further examine the role of UNICEF in overcoming sanitation problems in India through the WASH Program. The method used in this study uses qualitative methods to explain systematically and factually. This study uses the theory of the Role of International Organizations. This theory is used to explain and emphasize UNICEF in carrying out its roles based on the values ​​set by international organizations.